The influence of ground motion duration on the energy based assessment of buildings with infill walls. (March 2023) - Balun, Bilal
Abstract: Infill walls are often used in buildings to divide the residential area in order to meet the architectural requirements and are considered as non-bearing structural elements. In some buildings, infill walls are not used in the frames of the ground floors for commercial or other architectural purposes. Thus, vertical infill wall discontinuity is formed and it appears as an irregularity by earthquake regulations. At the same time, this situation has caused damage to the structures in some earthquakes. Nowadays, traditional seismic design based on strength and resistance is considered not an adequate way to design structures under earthquake effects. Besides, the role of ground motion duration on the seismic performance of building structures has been subject of research recently. One of the methods of defining damage in earthquake resistant design is the energy approach. For this purpose, in this study, the effect of infill walls on the seismic assessment of structures exposed to short and long duration ground motions was performed on dissipated seismic energy approach. Nonlinear time history analyses were performed in two cases, fully infilled and infilled except for the ground floor. Classification of ground motion durations is based on a threshold of 25 s of significant duration (D5-95 ), and ground motions were evaluated as two different recording pairs of short and long duration. Using spectrally matched short and long duration earthquake records, nonlinear time history analyses were performed for building models and the results were evaluated over hysteretic energy. The analyses showed that the hysteretic energy demands depend on both the ground motion duration and the infill wall placement in the building.